Pagar Budaya dalam Rukat Bumi: Strategi Pemertahanan Identitas di Desa Tlekung dan Kelurahan Sukun - Teddy Afriansyah; Lina Puryanti; Sarkawi B. Husain (Laboratory of Anthropology Department, Faculty of Humanity, Halu Oleo University, 2025)
The Rukat Bumi tradition in Tlekung Village and Sukun Village holds deep cultural significance for the local community. However, challenges to its sustainability cannot be overlooked. This study aims to: (1) explain the implementation of Rukat Bumi in Tlekung Village and Sukun Village, and (2) explain adaptive strategies to preserve its cultural identity. Using a descriptive qualitative approach, the study finds that Rukat Bumi in Tlekung Village is conducted in a pavilion where the community gathers for a communal meal. In contrast, in Sukun Village, that tradition involves a procession through the village streets, featuring offerings of crops, particularly a large tumpeng. To ensure the continuity of Rukat Bumi, several adaptive strategies have emerged, including (a) education, (b) leveraging social media, (c) collaboration with various stakeholders, and (d) the development of creative products. Addressing the challenges faced by Rukat Bumiin both locations has significant implications for cultural preservation. Moreover, implementing adaptive strategies not only sustains cultural identity but also fosters an inclusive space for that tradition to thrive across generations.